Efficiency Analysis Sand and Stone Mining: Production Stochastic Frontier Modeling - Elya Nurul Amalia; Nunik Kadarwati; Suharno Suharno (Jurnal Akuntansi, Manajemen dan Ekonomi, 2022)
This research aims to analyze the effect of capital, cost, working hours, labor, technology, analyze the most influential variables on the production of sand and stone and determine the level of technical efficiency, allocative efficiency, and economic efficiency. The analysis technique uses the Stochastic Frontier Analysis MLE method. The results showed that capital, cost, and technology variables have no significant effect, labor has a positive and significant effect. The most influential variable on sand and stone production in Banyumas Regency is labor. The level of technical efficiency in the production of sand is 0,829418, and stone is 0,743271. The level of allocative efficiency of sand production is 1,799976 and stone 1,997888. The level of economic efficiency of sand production is 1,492933 and stone 1,484972. The production of sand and stone has reached technical efficiency but has not yet reached allocative efficiency and economic efficiency.